S1_6 Iceman - Kelliher, Ruth; Geddes, Alex; Cox, Gavin; Peterson, Phil (Physics Special Topics, 2009)
This article investigates the physics behind x-men’s Iceman and his ability to produce ice out of the air. Some theoretical ideas to explain the anomaly are suggested. It is concluded that, although he is a genetically advanced human, Iceman is still human and so the energy required to produce any significant amount of ice (being >1kg) is unrealistic and too high to be of any practical use.Â Â 